Antimicrobial peptide isolated from Bacillus amyloliquefaciens K14 revitalizes its use in combinatorial drug therapy - Regmi, Sudip; Choi, Yun Hee; Choi, Yoon Seok; Kim, Mi Ri; Yoo, Jin Cheol (Folia microbiologica, 2017)
The present study was performed to evaluate the antibacterial activities of an antimicrobial peptide (CSpK14) and the synergies thereof with β-lactams against vancomycin-resistant Staphylococcus aureus (VRSA) and Enterococci (VRE). Our strain was isolated from fermented food (kimchi), which is 99.79 % homologous with Bacillus amyloliquefaciens subsp. plantarum FZB42(T). CSpK14 was purified to homogeneity by diammonium sulfate precipitation, concentration, dialysis, and followed by two-stage chromatographic separation, i.e., Sepharose Cl-6B and Sephadex G-25 chromatography, and had a molar mass of ~4.6 kDa via Tricine SDS-PAGE and in situ examination. It was stable at pH 6.0-11.5 and temperature up to 80 °C. In addition, it was also stable with various metal ions, solvents, and proteases. The N-terminal amino acid sequence was H-Y-D-P-G-D-D-S-G-N-T-G and did not show any significant homology with reported peptides. However, it shows some degrees of identity with alpha-2-macroglobulin and ligand-gated channel protein from different microorganisms. CSpK14 significantly reduced the minimum inhibitory concentrations (MICs) of β-lactams and had no effect on non-β-lactams against VRSA and VRE. MICs of CSpK14/oxacillin and CSpK14/ampicillin were reduced by 8- to 64-fold and 2- to 16-fold, respectively. The time killing assay between CSpK14/oxacillin (2.29-2.37 Δlog10CFU/mL at 24 h) and CSpK14/ampicillin (2.30-2.38 Δlog10CFU/mL at 24 h) being >2-fold and fractional inhibitory concentration index ˂0.5 revealed synergy. Furthermore, the biofilms formed by VRSA and VRE were reduced completely. CSpK14 was simple to purify, had low molecular mass, was stable over a wide pH range or tested chemicals, had broad inhibitory spectrum, and possessed potent synergistic antimicrobial-antibiofilm properties. CSpK14 synergistically enhanced the efficacy of β-lactams and is therefore suitable for combination therapy.
Keywords: oxacilin; Ampicillin; mikrobiální testy citlivosti; stabilita proteinů; Oxacillin; chromatografie iontoměničová; sekvence aminokyselin; kationické antimikrobiální peptidy; Protein Stability; Bacillus amyloliquefaciens; Anti-Bacterial Agents; Amino Acid Sequence; Staphylococcus aureus; Phylogeny; Microbial Sensitivity Tests; Vancomycin Resistance; Vancomycin-Resistant Enterococci; Drug Synergism; kombinovaná farmakoterapie; synergismus léků; Antimicrobial Cationic Peptides; biofilmy; antibakteriální látky; fylogeneze; Biofilms; enterokoky rezistentní vůči vankomycinu; Chromatography, Ion Exchange; ampicilin; rezistence na vankomycin; Drug Therapy, Combination